Innovative Approaches to Post-Earthquake Reconstruction Material Evaluation for Healthy Simple Houses - Junita Eka Susanti; Miskar Maini; Elian Zhafira (G-Tech: Jurnal Teknologi Terapan, 2025)
Post-earthquake housing reconstruction is essential for accelerating community recovery and ensuring safer living conditions in disaster-prone regions. This study evaluates the potential of recycled rubble sand from demolished masonry walls as an acceptable aggregate replacement in mortar production. It explores its integration into the development of a Healthy Simple House (HSH) model for post-disaster housing reconstruction. Laboratory experiments were conducted in accordance with PUBI-1982 and SII 0052-80 standards to characterize material properties and assess mechanical performance. The results indicate that rubble sand exhibits a well-graded particle distribution, stable density values (SSD 2.48 g/cm³, bulk 2.35 g/cm³, apparent 2.71 g/cm³), and moderate water absorption (5.62%), with slight organic contamination. Compressive strength tests showed that mortars with a 1:3 cement-to-sand ratio reached approximately 24 MPa at 28 days, meeting structural requirements, while higher rubble proportions reduced strength, restricting their application to non-structural components. The incorporation of rubble sand into the HSH model highlights its role in sustainable reconstruction by reducing reliance on natural resources while ensuring safe, healthy, and affordable housing. The study concludes that recycled rubble sand can be effectively utilized as a partial aggregate substitute, providing practical guidance for post-disaster housing programs and informing policy development for environmentally friendly and resilient reconstruction strategies that contribute to community resilience.